LEXICAL SEMANTICS: ANALYZING LEXICO-SEMANTIC TYPES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Lexical semantics is a subfield of linguistics that focuses on the meaning of words and the relationships between them. Central to this area of study is the analysis of lexico-semantic types, which categorize words based on shared semantic properties. This article explores the concept of lexico-semantic types, outlining the main categories such as nouns, verbs, adjectives, adverbs, and function words, and discussing how words are grouped according to their meanings and syntactic roles. It also examines the relationships between lexical items, including synonymy, antonymy, hyponymy, polysemy, and collocation, providing a deeper understanding of how meaning is structured within the lexicon. By analyzing these types, the article emphasizes their importance in both theoretical linguistics and practical applications, such as natural language processing and language teaching